Analisis Visual Infografis Produk “Samsung Galaxy Note Edge” - Pungky Febi Arifianto (AKSA: Jurnal Desain Komunikasi Visual, 2018)
This research aims to figure out the understanding and the comprehending process of infographic used in samsungtommorow.com as its marketing medium in a way to show product excellency through the territory of semiotic meaning, specifically connotative meaning. Based on the observation, it can be concluded that Samsung as manufacturer use infographic as a problem solver in communication problem. Infographic also give the general overview of the definition as a form of communication through visual sign. Infographic can also produce information and marketing process that shown by the signs that appear in symbols. Signs that appear in infographic are not only express the denotative meaning as what it is, but it can be more than that. The message contained in infographics can be dismantled by doing thorough observation of the object of visual signs inside, resulting in connotative meanings which can not be predicted to be correlated with the verbal language. To determine the connotative meaning that is generated through a visualization that is present in these infographics a theory is needed . In this case, the main theory used is the connotative meaning with social codes Rolland Barthes theory. The signs definition that generated by design communication visual will be assisted by th